Canonical Translation - Júlio Cesar Neves Monteiro (Cadernos de Tradução)
The discussion about the status of the translated literary text and the position of the translator is ever-present in the field of Translation Studies. Sensitive issues such as authorship, authorship in translation and the position of the translated text within the receiving literary system keep theoreticians busy, as well as discussions about canon in literature and canon in translated literature. A less evident topic is the existence of canonical translations which are regarded as “definitive” in the receiving literary system or as a model for subsequent translations. I intend to show in this paper that the phenomenon I call canonical translation is neither an isolated phenomenon nor restricts itself to peripheral literary systems.